Innovative therapeutic strategies for cervical cancer: advances in pain management, angiogenesis inhibition, and peptide-based therapies - Beatrice Odei-Mensah; Samson A. Adeyemi; Lindokuhle M. Ngema; Hillary Mndlovu; Yahya E. Choonara (Biofunctional Materials)
Cervical cancer remains a major global health burden, particularly in low-resource settings, with a prevalence of 11.7%. Persistent infection with high-risk Human Papillomavirus (HPV) strains is the primary cause, affecting approximately 660,000 women and resulting in nearly 350,000 deaths annually. The disease is often accompanied by complex pain patterns due to tumour progression, nerve invasion, and treatment-related effects, which conventional therapies fail to adequately address. The burden of cervical cancer is disproportionately high in low- and middle-income countries (LMICs), where limited access to preventive healthcare, early screening, and effective treatment exacerbates the challenge. Current treatment modalities, including surgery, chemotherapy, and immunotherapy, are associated with significant limitations such as systemic toxicity, long-term complications, and inadequate pain relief. Traditional pain management approaches, including opioids and adjuvant analgesics, are often insufficient and accompanied by severe side effects, necessitating the exploration of novel therapeutic strategies. Emerging treatment options, such as cannabinoid-based analgesics, vascular endothelial growth factor (VEGF) inhibitors for angiogenesis suppression, and peptide-based drug delivery systems, offer promising alternatives for improving patient outcomes. These multimodal approaches aim to enhance therapeutic efficacy while minimizing systemic toxicity and treatment-related pain. This review explores innovative therapeutic strategies for cervical cancer management, with a focus on recent advancements in pain relief, angiogenesis inhibition, and peptide-based therapies. It synthesizes current research findings, identifies critical knowledge gaps, and outlines potential future directions to improve treatment effectiveness and overall patient quality of life.